The favor of friends : intercession and aristocratic politics in Carolingian and Ottonian Europe - Gilsdorf, Sean, 1966- (Brill's series on the early Middle Ages, 2014)
This book offers the first book-length exploration of intercession- aid and advocacy by one individual or group in behalf of another-within early medieval aristocratic societies. Drawing upon a variety of disciplines and historiographical traditions, Sean Gilsdorf demonstrates how this process operated, and how it was ideologically elaborated, in Carolingian and Ottonian Europe, allowing individuals and groups to leverage their own, limited interpersonal networks to the fullest, produce new relationships, gain access to previously closed spaces, and generate interest in their agendas from those able to effect change. This book enriches our understanding of early medieval politics and rulership, offering a model of political interaction in which hierarchy and comity do not stand in ideological and pragmatic tension, but instead work in integrated and mutually-reinforcing ways.